Pengaruh Motivasi Terhadap Hasil Dan Prestasi Belajar Mahasiswa - Ayu Putri Julia; Fitri Hayati (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2022)
The students' own encouragement or willingness to attend lectures in accordance with their own wishes, as well as the capacity to identify interests, skills, and restore their lives in the future, are all factors in the motivation of students to attend lectures.The level of humanity at which students accept, reject, and evaluate the knowledge they acquire through the teaching and learning process is called learning achievement.This study aims to determine how motivation influences student performance and learning outcomes.Researchers employ literature reviews from a variety of journals as their method.The study's findings regarding the impact of motivation on student achievement and learning outcomes are accurate.